2021
DOI: 10.1093/sleep/zsab252
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral therapy for insomnia has sustained effects on insomnia, fatigue, and function among people with chronic heart failure and insomnia: the HeartSleep Study

Abstract: Study Objectives Insomnia is common among adults with chronic heart failure (HF) and associated with daytime symptoms and decrements in function. The purpose of this randomized controlled trial (RCT) was to evaluate the sustained effects over one year of CBT-I (Healthy Sleep: HS) compared with HF self-management education (Healthy Hearts; attention control: HH) on insomnia severity, sleep characteristics, symptoms, and function among people with stable HF. The primary outcomes were insomnia s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 63 publications
5
68
0
Order By: Relevance
“…Although posttreatment levels of sleep impairment and sleep duration were not sustained, levels approximated normal levels during the pandemic. These finding confirm the clinical benefits of CBT-I for people with HF and comorbidities 13 , 27 and also suggest the potential benefits of HF self-management education. Given our findings, future prospective studies are needed to examine the extent to which these and other behavioral interventions improve the ability of people with HF to manage stressful events, such as the pandemic.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Although posttreatment levels of sleep impairment and sleep duration were not sustained, levels approximated normal levels during the pandemic. These finding confirm the clinical benefits of CBT-I for people with HF and comorbidities 13 , 27 and also suggest the potential benefits of HF self-management education. Given our findings, future prospective studies are needed to examine the extent to which these and other behavioral interventions improve the ability of people with HF to manage stressful events, such as the pandemic.…”
Section: Discussionsupporting
confidence: 78%
“…We included participants with no or no more than mild untreated sleep-disordered breathing and those treated with continuous positive airway pressure. We excluded people with seizure disorders, severe sleepiness, narcolepsy, end-stage renal failure, bipolar disorder, severe depression, current illicit drug use, restless leg syndrome, and/or more than mild untreated sleep apnea, and people working nights or shift work 13,14 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, several studies have been conducted investigating the effect of CBT on mental health status and its indicators in patients. For example, Redeker et al, found that CBT had a significant effect on the improvement of fatigue, insomnia, and performance in patients (Redeker et al, 2021). Numerous studies, such as those done by Heslop‐Marshall et al (2021), Fenlon et al (2020), and Siebmanns et al (2021), also acknowledged that nurses were capable of performing this therapeutic intervention in the clinical settings.…”
Section: Introductionmentioning
confidence: 99%